Investigating the characteristics of residential end uses of water: A worldwide review - Mazzoni, Filippo; Alvisi, Stefano; Blokker, Mirjam; Buchberger, Steven G.; Castelletti, Andrea; Cominola, Andrea; Gross, Marie-Philine; Jacobs, Heinz E.; Mayer, Peter; Steffelbauer, David B.; Stewart, Rodney A.; Stillwell, Ashlynn S.; et al. (Water research (Oxford), 2023)
•We systematically review 114 studies on the residential end uses of water.•We develop a multi-level analysis to compare the outcomes available in the literature.•The study allows understanding the most investigated aspects of water end uses.•Features from different geographical and cultural regions of the world are explored. A detailed characterization of residential water consumption is essential for ensuring urban water systems' capability to cope with changing water resources availability and water demands induced by growing population, urbanization, and climate change. Several studies have been conducted in the last decades to investigate the characteristics of residential water consumption with data at a sufficiently fine temporal resolution for grasping individual end uses of water. In this paper, we systematically review 114 studies to provide a comprehensive overview of the state-of-the-art research about water consumption at the end-use level. Specifically, we contribute with: (1) an in-depth discussion of the most relevant findings of each study, highlighting which water end-use characteristics were so far prioritized for investigation in different case studies and water demand modelling and management studies from around the world; and (2) a multi-level analysis to qualitatively and quantitatively compare the most common results available in the literature, i.e. daily per capita end-use water consumption, end-use parameter average values and statistical distributions, end-use daily profiles, end-use determinants, and considerations about efficiency and diffusion of water-saving end uses. Our findings can support water utilities, consumers, and researchers (1) in understanding which key aspects of water end uses were primarily investigated in the last decades; and (2) in exploring their main features considering different geographical, cultural, and socio-economic regions of the world. [Display omitted]